The role of general change mechanisms in sudden gains in the treatment of anorexia nervosa - Brockmeyer, Timo; Titzmann, Marieke; Zipfel, Stephan; Wild, Beate; Resmark, Gaby; Teufel, Martin; Giel, Katrin; de Zwaan, Martina; Dinkel, Andreas; Herpertz, Stephan; Burgmer, Markus; Löwe, Bernd; et al. (Behaviour research and therapy, 2023)
Previous research has shown a robust association between sudden gains (SGs) and treatment outcome in psychotherapy for various mental disorders including anorexia nervosa (AN). However, little is known about factors contributing to SGs. This study investigated the role of general change mechanisms in body-weight related SGs in AN. Data were drawn from a randomized-controlled trial on cognitive-behavioral therapy (CBT) and focal psychodynamic therapy (FPT) for adult outpatients with AN. Session-level data on the general change mechanisms ‘clarification’ (insight), ‘mastery’ (coping), and ‘therapeutic relationship’ were analyzed. Pre-gain sessions were compared with control (pre-pre-gain) sessions in 99 patients with a SG in body weight. Additionally, propensity score matching was used to compare data from pre-gain sessions from 44 patients with SG and data from the corresponding session from 44 patients without SG. In the pre-gain session, patients experienced higher levels of clarification and mastery but not therapeutic relationship. Compared to patients without a SG, patients with a SG likewise experienced more clarification and mastery but not a better therapeutic relationship in the pre-gain/corresponding session. CBT and FPT did not differ regarding these effects. The findings suggest that general change mechanisms contribute to SGs in CBT and FPT for AN.